Comparison of the Efficiency of Using the Cash Flow Accounting Method and the Accrual Method for Financial Recording of MSMEs in Mataram City - Nabila Fadilah; Herlina Pusparini (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study compares the efficiency of the cash flow accounting method and the accrual method in recording the finances of Micro, Small, and Medium Enterprises (MSMEs) in Mataram City. The results show that the majority of MSMEs still use the cash flow method because it is simpler, easier to implement, and does not require complex accounting expertise. Although operationally efficient, the cash flow method has limitations in presenting comprehensive financial information. In contrast, the accrual method is able to present more complete and accurate financial information because it records transactions based on rights and obligations, not just cash flow. The accrual method is considered more appropriate for MSMEs that want to develop professionally and collaborate with formal financial institutions. Therefore, the choice of financial recording method should be adjusted to the business scale, information needs, and long-term goals of each MSME.